Functional expression of the Chlorella hexose transporter in Schizosaccharomyces pombe. - Sauer, Norbert; Caspari, Thomas; Klebl, Franz; Tanner, Widmar (Proceedings of the National Academy of Sciences of the United States of America, 1990)
Schizosaccharomyces pombe cells were transformed with an S. pombe expression vector containing a full-length cDNA of the Chlorella hexose transporter. The transformed cells accumulated 3-O-methylglucose up to 10-fold, whereas wild-type S. pombe and control transformants could only equilibrate this sugar analogue. In a pH-jump experiment, in which extracellular pH was lowered by 1.9 units, the accumulation ratio was increased in transformed cells but not in control cells. This result indicates that the gene product, Chlorella H+/glucose-symporter protein, and a pH gradient suffice for active sugar uptake. Km values for glucose, 6-deoxyglucose, and 3-O-methylglucose of 1.5 x 10(-5) M, 2.7 x 10(-4) M, and 1.0 x 10(-3) M, respectively, were identical in Chlorella and in S. pombe cells transformed with Chlorella cDNA and approximately 100-fold lower than those of the endogenous transport system of S. pombe.